Muslim spiritual care during pandemics: a study of Muslim early works - Bensaid, Benaouda; Machouche, Salah (AHAS KIRKHS, 2022)
The study of spirituality continues to draw increased academic interest, especially in the way it defines the meaning and purpose of life, mould both thinking and emotions, motivates and drives actions, shapes human relations, and sustain life balance and wellbeing. In the context of the Muslim faith, Muslims are encouraged to nurture their moral character, cultivate their spiritual discipline, and engage in the overall betterment of their quality of life. The methodical individual and collective religious practices which feed and at the same time sustain Muslim spirituality represent an ever-evolving state proportionately resonating with one's spiritual commitment, dedication, and actions. During times of tribulations, crises, or pandemics, however, spirituality appears to play a critical role in Muslims' processes of coping, managing, and community support. This study investigates the works of early Muslim scholars with regards to the conception and approach to pandemics, and the categories of spiritual support and practices they prescribed for coping and mitigating the many adverse effects of crises related stress and anxiety on mental health and wellbeing.